The Relationship Between TQM And Business Performance: The Mediating Role of Innovation Performance and Organizational Learning Culture: A Pitch - Hafiz Ahmad Ashraf (Journal of Accounting and Management Information Systems (JAMIS), 2021)
This pitch research letter (PRL) is shaped by the pitch mold initiated by Faff (2015, 2019), for the proposed research project on the relationship between total quality management (TQM) and business performance: The mediating role of innovation performance and organizational learning culture (OLC) in developing countries. The beginning includes the antecedents enforcing my pitch motivations for doing pitch work. This PRL shows that pitch template is a modern style of researching as it starts from the proposal and has the power of dissertation defense. This PRL will shadow some of my research work and some personal reflections about the importance of the pitch template.
Keywords: L1; L15; 650; Pitch Research Letter; TQM; Microfoundations of institutional theory